1974
DOI: 10.2135/cropsci1974.0011183x001400010030x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Variability of Quantitative Traits in BSSS by Using Unselected Maize Inbred Lines1

Abstract: We evaluated 247 $" unselected maize (Zea mays L.) lines, developed by single-seed descent from 250 'BSSS' S 0 plants, for 21 quantitatively inherited traits in 3 environments. The S fl lines were considered representative of a random group of genotypes from BSSS for the estimation of genetic variances, heritabilities, and correlations among traits.Significant genetic variation existed among the S 6 lines for all traits. The estimates of heritabilities, on a mean basis, were high for most traits, indicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
4

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 0 publications
4
21
0
4
Order By: Relevance
“…Increases in ear length, ear diameter, cob diameter,, kernel depth, and kernel row number associated with recurrent selection for grain yield, although usually statistically significant, were of small magnitudes (Table 21). Statistically significant correlation coefficients between grain yield and ear and kernel traits, often, have been reported (Obilana and Hallauer, 1974;Crosbie, 1976;Gama, 1976). Proportion of grain-yield variation attributable to these traits, however, is usually small and is highly influenced by genotype x environment interactions (Obilana and Hallauer, 1974).…”
Section: Number Of Ears Per 100 Plants Increased As Recurrent Selectimentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in ear length, ear diameter, cob diameter,, kernel depth, and kernel row number associated with recurrent selection for grain yield, although usually statistically significant, were of small magnitudes (Table 21). Statistically significant correlation coefficients between grain yield and ear and kernel traits, often, have been reported (Obilana and Hallauer, 1974;Crosbie, 1976;Gama, 1976). Proportion of grain-yield variation attributable to these traits, however, is usually small and is highly influenced by genotype x environment interactions (Obilana and Hallauer, 1974).…”
Section: Number Of Ears Per 100 Plants Increased As Recurrent Selectimentioning
confidence: 99%
“…Statistically significant correlation coefficients between grain yield and ear and kernel traits, often, have been reported (Obilana and Hallauer, 1974;Crosbie, 1976;Gama, 1976). Proportion of grain-yield variation attributable to these traits, however, is usually small and is highly influenced by genotype x environment interactions (Obilana and Hallauer, 1974). In my study, significant genotype x nitrogen and genotype X density interactions were observed for ear length (Table 23).…”
Section: Number Of Ears Per 100 Plants Increased As Recurrent Selectimentioning
confidence: 99%
“…Tanaka and Yamaguchi (1972) previously concluded that sink size as determined by number of kernels per unit field area was a limitation to increased grain yields. Significant correlations between sink strength and grain yield also have been reported by El-Lakany and Russell (1971), Obilana and Hallauer (1974), Hallauer (1971), Crosbie et al (1978a) and Crosbie and Mock (1980). Different sink strength traits were correlated with grain yield in dif ferent maize populations, however.…”
Section: Discussionmentioning
confidence: 51%
“…Root damage displayed the lowest estimates of heritability. Owens (1971) and Obilana and Hallauer (1974) also found that among the rootworm resistance characters in BSSS com populations, root damage had the lowest estimated heritability. Estimates of heritability reported by Owens (1971) for those three root characters were relatively lower than those found in this study although similar families were used, but the estimates based on lines pre sented by Obilana and Hallauer (1974) were higher.…”
Section: Field Data and Analyses Of Variancementioning
confidence: 93%